KOMITMEN INDONESIA DALAM RATIFIKASI PARIS AGREEMENT: ANALISIS YURIDIS DAN IMPLEMENTASI KEBIJAKAN PENURUNAN EMISI KARBON - Loso Judijanto (INTELIGENSIA MEDIA, 2025)
Indonesia's ratification of the Paris Agreement through Law No. 16 of 2016 demonstrates a strong legal commitment to reducing greenhouse gas emissions. This study uses a literature review method to analyse two main aspects, namely a legal analysis of ratification and the implementation of carbon emission reduction policies. The legal analysis highlights the compatibility of ratification with national law and Indonesia's obligations, while policy implementation examines strategies such as Nationally Determined Contributions (NDCs) and carbon pricing regulations. The results of the study indicate that ratification provides a solid legal basis for Indonesia's climate commitments and requires harmonisation with national policies. Policy implementation shows progress through various programmes, but faces challenges in coordination, capacity, and financing. Carbon trading mechanisms and energy transition are key to achieving emission targets. In conclusion, Indonesia's commitment through ratification has been translated into legal actions and concrete policies to reduce emissions. However, achieving targets requires enhanced stakeholder synergy, regulatory harmonisation, capacity strengthening, and sustainable financing. This study provides strategic input for the development of Indonesia's climate policy going forward.